Antibacterial Activity of Nisin-Silver Nanoparticles on Staphylococcus epidermidis and Therapeutic Effects in Experimental Skin Infection in Mice - Ahmed Qassim Al-Awadi (Journal of Global Pharma Technology, 2016)
Today technology using nanoparticle when treatment pathogentic microorganism and we focused on this here .It was found that the species of Staphylococcus epidermidis used in present study were sensitive to Levofloxacin .The aim of report effect (Nisin-Silver Nanoparticles) on ability of complete healing injury comparing using Nisin only. In vivo study revealed that silver nanopasrticles treatment of S. epidermidis contaminated injured skin showed good healing process contain complete regeneration of the epithelial cells of the epidermis and good prognosis and increase of cellulartiy of the dermal content compared with untreated group. In conclusion, treatment of skin infected with S.epidermidis using silver nanoparticles at different concentration may limit the skin damage, localized the lesion to the incision site and enhance the healing process.Key words: Staphylococcus epidermidis, Nisin A, silver nano particles.